COMMUNICATION OF MUTUAL ASSISTANCE IN THE MELEMANG TRADITION OF KARANG RAJA MUARA ENIM VILLAGE - Desy Misnawati (Universitas Padjadjaran, 2023)
This study aims to elucidate the communication pattern of the lemang tradition of mutual aid as a cultural inheritance passed down from generation to generation in Karang Raja Village, Muara Enim Regency, South Sumatra. This cooperation communication research is qualitative in design, with the object of study being cooperation activities in the lemang tradition. Residents of Karang Raja Village served as research subjects. Non-participant observation, interview approaches, and document analysis were employed to collect data from three critical informants. The data analysis technique uses the Miles and Huberman interactive model, which goes through data reduction, data display, verification, and concluding. The study’s findings show that: 1) the lemang tradition is an ancestral heritage with symbols associated with religious, customary, and social values; 2) mutual cooperation communication is an inseparable part of the lemang tradition itself, which is the behavior of togetherness, kinship, loyalty, and the culture of eating together with the people of Karang Raja Village; and 3) the communication pattern of gotong royong that was formed was carried out by the people of Karang Raja Village before and after the implementation of the lemang tradition on 10 Muharram. These three things demonstrate the residents of Karang Raja Village’s devotion to the identity of regional traditions passed down through centuries, constantly living in harmony, peace, and a high level of cohesiveness. The study’s conclusion shows that the lemang tradition reflects the communication of mutual cooperation carried out from generation to generation and tends to have a vertical pattern.